The toxicology and detoxification of Gelsemium: Traditional and modern views - Chong-Yin Huang; Si-Juan Huang; Hui Yu; Mo-Huan Tang; Zhao-Ying Liu (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Gelsemium, a whole grass in the family Loganiaceae, is the world's poisonous plants. Due to its flower's resemblance to honeysuckle, there has been a rise in cases of accidental ingestion of Gelsemium, leading to poisoning and even fatalities in recent years. Although this problem has been apparent for many years, there is now promise that it can be better understood. This work seeks to comprehensively summarizes. Methods: References for this review were collected by searching CNKI (http://www.cnki.com.cn) and PubMed untill 29 October 2023. The selection of articles was performed by reading the title, abstract, and keywords. Results: Gelsedine-type alkaloids are identified as the primary toxic constituents in Gelsemium. Animal experimentation has elucidated the acute neurotoxic impact of Gelsemium, primarily characterized by inhibition of the respiratory center. This effect may be intricately linked to the disruption of GABA/Glu equilibrium and NMDA receptor-mediated excitotoxicity. Some studies have found the potential reduction of toxicity in Gelsemium through processing and compatibility with traditional Chinese Medicine. However, prompt endotracheal intubation and mechanical ventilation are paramount in clinical instances of Gelsemium poisoning. Additionally, there is evidence supporting the efficacy of enhancing CYP3A4/5 enzyme metabolism can diminish the concentration of Gelsemium and mortality rates from poisoning. Discussion: This review provides a summary of clinical symptoms and rescue measures for Gelsemium poisoning, aiming to enhance treatment options and mitigate toxic effects. The elucidation of Gelsemium's neurotoxic mechanism may offer insights for future research, particularly in understanding Gelsemium's regulatory role on GABA receptor and NMDA receptor, which is expected to identify and develop specific antidotes for Gelsemium poisoning.